Videoforskning på ulike læringsarenaer Mangfoldig videodata i pedagogisk forskning og utvikling - Rusk, Fredrik (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2021)
This book presents wide-ranging video research in pedagogical contexts that have previously received little notice. Video research is, and can be employed for, so much more that standing in a classroom and filming with a camera. That is what we hope to achieve with this book - to demonstrate the inherent flexibility in video, that it can serve as one tool among many and be utilized in a variety of settings in several different ways. We want to emphasize the fact that you don't need a professional lab with lots of equipment to do quality video research. All you need is a camera, a microphone, and a good plan for what you can, and cannot, capture in your project. Video Research in Educational Settings: Diverse Video Data in Pedagogical Research and Development is written primarily for other researchers, including those who are just beginning their research activities (such as master students and PhD candidates) and are interested in discovering how flexible, applicable and creative data collection can be with the help of video, and how rich the data material one obtains can be. The chapters represent a broad cross-disciplinary approach, yet with one common denominator: the use of video in different educational arenas, not only for data collection, but also for stimulating reflection, learning and greater expertise.